Design Combination Attributes (Stimuli) of Sweet Potatoes Product Using Syntax and Orthogonal Procedure - Ihwah, Azzimatul; Astuti, Retno; Effendi, Usman; Rohmah, Wendra G.; Effendi, Mas'ud (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
Processed orange sweet potato has produced people who joined in Gapoktan Sukoanyar Village, District Pakis, Kab. Malang, among others stick, lunkhead, crackers. In the meantime, orange sweet potato processed products they produce only deposited in Food Production and Training Center (FPTC) owned THP FTP UB Department. However, manufacturers have complained that the production capacity and the number of products sold is still unbalanced. In other words, many products are not sold, while the product has been distributed to FPTC not all sold out. The purpose of this study to find out what the consumer desires, and obtain the design combination of attributes (stimuli) sweet potato processed products. The population in this study is a population of Malang. The size of the sample to be taken, calculated using the formula Slovin. By using a significance level of 5% was obtained sample size of 400. The sampling technique used is non-probability sampling, the purposive sampling. So respondents will be used for the sample of respondents who like sweet potatoes. The questionnaire was given to a number of respondents. Questions in the questionnaire is an open question. From the results of the questionnaire, obtained 4 levels of attributes that taste, price, type and how to purchase. 4 levels of attributes and levels, gained as much as 16 combinations of attributes (stimuli), both designed using procedures and orthogonal syntax, whereas if only used 3-level attributes, ie taste, price and type of the obtained 8 stimuli if designed using a procedure syntax and 7 stimuli if designed using orthogonal procedure.Keywords: attributtes product, sweet potatoes, stimuli, syntax, orthogonal